2014
DOI: 10.2472/jsms.63.816
|View full text |Cite
|
Sign up to set email alerts
|

Free-Edge Stress Singularity of Bonded Dissimilar Materials with an Interlayer under Thermal Stress Loading

Abstract: Free-edge stress singularity usually develops near the edge of interface of bonded dissimilar materials. Because of the difference of the coefficient of the thermal expansion of the materials, the residual stress may develop when two materials are bonded. To defuse the residual stress, an interlayer may be inserted between the two materials. Stress distribution near the edge of the interface in the presence of the interlayer is very important to evaluate the strength of the bonded dissimilar materials. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…From Fig. 7, it is found that the order of the singularity can be correctly identified, even if the initial value of the order of the singularity λ (1) is greater than the target value.…”
Section: Numerical Experimentsmentioning
confidence: 95%
See 3 more Smart Citations
“…From Fig. 7, it is found that the order of the singularity can be correctly identified, even if the initial value of the order of the singularity λ (1) is greater than the target value.…”
Section: Numerical Experimentsmentioning
confidence: 95%
“…The computational flow of the identification analysis of the order of singularity is shown below. (1) The initial order of the singularity {λ} (1) and convergence criterion ϵ are input.…”
Section: Identification Of Order Of Singularitymentioning
confidence: 99%
See 2 more Smart Citations